Increased impact for Open Publishing - Mikki, Susanne; Zygmuntowska, Marta (Septentrio Conference Series, 2017)
Watch the VIDEO here. Presenter - Susanne Mikki. Purpose Based on the scholarly output in Norway, we aim to determine the total amount of articles freely available online, and prove whether there exists a citation advantage for these. We also investigate whether these articles receive more mentions on social platforms such as tweets or blogposts. Design The total scholarly publication output of Norway is indexed in CERES, the Current Information System in Norway. Based on these publication data, we searched a) Google Scholar and denoted a document as freely available, when a link to a full-text was provided, and b) altmetric.com to detect mentions of these articles. We analyzed the extracted data by publishing year, citations, availability, provider and mentions on different platforms. Findings Dependent on subject field, we find that almost 70 % of all articles are freely available. Articles behind paywalls belong to the most prestigious publishers such as Elsevier, Springer, Routledge and Universitetsforlaget (the main Norwegian academic publisher). According to Google Scholar’s link resolver, ResearchGate and academia.edu are the most frequent providers. In addition, institutional repositories seem to play a major role in posting free article versions. We find a clear advantage for open publishing; on average, these documents received almost 30 % more mentions on social media platforms and twice as many citations, indicating that open access is the future in publishing.